New Subclass of Analytic Function Involving q-Mittag-Leffler Function in Conic Domains - Saima Noor; Asima Razzaque (Journal of Function Spaces)
In this paper, we formulate the q-analogus of differential operator associated with q-Mittag-Leffler function. By using this newly defined operator, we define a new subclass k−USq,γmα,β, of analytic functions in conic domains. We investigate the number of useful properties such that structural formula, coefficient estimates, Fekete–Szego problem and subordination result. We also highlighted some known corollaries of our main results.